Evaluación del rendimiento de la arquitectura de seguridad INDECT (2018)
This paper evaluates the performance of the key elements of the security architecture developed by the INDECT project. In particular it first evaluates three different concurrent error detection mechanism (parity check, Berger code, and cyclic redundancy check) developed in software- and hardware-based implementations of the INDECT block cipher. It also analyses the performance hit in secure web servers when enabling TLS/SSL with mutual authentication. Finally, it evaluates the throughput and delay of traffic in the virtual private network based on the OpenVPN software package with the implemented INDECT block cipher. The results of these evaluations demonstrate that the proposed mechanisms, and by extension the whole INDECT security architecture, are viable and can be used in high-performance Police information and communication systems.